Tracing the Path of Islamic Education Boarding School Research: a Bibliometric Analysis - Solichah, Etik Nur; Jinan, Mutohharun; Apriantoro, Muhamad Subhi; Ashfahany, Afief El (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to determine the mapping of the development and direction of Islamic Education Boarding School research on publications indexed by Scopus. This study used bibliometric analysis techniques to explore all publications indexed in Scopus' Islamic Education Boarding School database from 1990 to 2023. The data obtained were analyzed using Excel and R/R-Studio. VOSviewer analyzes the simultaneous occurrence of keywords and document citations visually. The author found 209 publications that fit the function, subject, and criteria set. The results of this study show an annual growth rate of 7.54%, with the most publications on Islamic Education Boarding School in 2022. Indonesia is the country that contributes the most publications with affiliations from the State University of Malang. Setyosari, P. became the most prolific writer on the theme of Islamic Education Boarding School.